Agricultural Credit in India in the 2000s: Growth, Distribution and Linkages with Productivity. (May 2016) - Misra, Rekha; Chavan, Pallavi; Verma, Radheshyam
The period of the 2000s witnessed a sharp revival in agricultural credit in India that was largely policy induced. There were emerging shifts in institutional, functional and regional distributions of agricultural credit during the decade. This study attempts to explore the relationship between agricultural credit and agricultural production/productivity. The state-level panel model attempted in this article suggests a positive impact of the intensity of agricultural credit on total factor productivity in agriculture. The impact was relatively stronger with respect to direct agricultural credit. A case study of the (combined) state of Andhra Pradesh also suggests a positive association between agricultural credit and agricultural production. The study lends credence to the policy approach of including agriculture, the largest employer in the Indian economy, as a sector for priority credit in India. It also highlights the point that the sector deserves continued policy support in order to move onto a sustainable and higher growth path. JEL Classification: Q10, Q14, Q18, N55